Environment-friendly heterogeneous alkaline-based mixed metal oxide catalysts for biodiesel production - Lee, Hwei Voon; Juan, Joon Ching; Yap, Taufiq Yun Hin; Ong, Hwai Chyuan (MDPI, 2016)
The critical problem arising from the depletion of fossil fuels has stimulated recent interests in alternative sources for petroleum-based fuel. An alternative fuel should be technically feasible, readily available, sustainable, and techno-economically competitive. Biodiesel is considered as a potential replacement of conventional diesel fuel, which is prepared from non-edible and high-acid feedstock via transesterification technology. The focus of this study is to investigate the catalytic activity of mixed metal oxides (MMOs) as catalysts for biodiesel production by using non-edible jatropha oil as feedstock. Various types of MMOs (CaO-MgO, CaO-ZnO, CaO-La2O3, and MgO-ZnO) were synthesized via a co-precipitation method. In this study, transesterification activities are closely related to the physicochemical properties of catalysts. The presence of different active metals in the binary system greatly influenced the surface area, basicity, and the stability of catalysts. The catalytic activity of MMO catalysts was increased in the order of CaO-ZnO (94% ± 1%) > CaO ~ CaO-MgO ~ CaO-La2O3 (~90% ± 2%) > MgO-ZnO (83% ± 2%) > MgO (64% ± 1%) > ZnO (41% ± 2%) > La2O3 (23% ± 1%). In addition, the MMO catalysts, especially CaO-ZnO, demonstrated high reusability and catalyst stability for four cycles of transesterification reaction of jatropha oil.